Molecular crosstalk - Hakeem, Khalid Rehman; Ibrahim, Faridah Hanum (Universiti Putra Malaysia Press, 2013)
Insects, like other organisms do not exist in isolation, but interact with many other species in their communities. Insect-plant interactions are common and widely distributed in nature. Some of these interspecific interactions, for example, plant associations with fungi in mycorrhizae or with insect pollinators - are mutually beneficial.